EFFECTIVENESS OF ROSELLA AS AN ANTIBACTERIAL - Karauwan, Sharron Imanuela; Andini, Shasya Putri; Erindra, Shafrina; Pakpahan, Evie Lamtiur (Universitas prof. Dr. Moestopo (Beragama), 2025)
The use of herbs for health maintenance and disease treatment is increasingly popular, particularly in developing countries. Rosella (Hibiscus sabdariffa L.) stands out as an herbal plant with significant health benefits. Its flower petals are rich in bioactive compounds, including flavonoids, saponins, tannins, anthocyanins, polyphenolic alkaloids, and terpenoids, which contribute to its antibacterial properties. The part of the rosella plant that is usually used is the petals. Rosella flower petals contain chemicals such as flavonoids, saponins, tannins, anthocyanins (red substances), polyphenolic alkaloids and terpenoids. The substances contained in the rosella plant have antibacterial activity. This paper discusses the antibacterial effect of the rosella plant. This study aimed to evaluate rosella’s antibacterial effectiveness by reviewing 15 sources published between 2012 and 2022 from Google Scholar and PubMed in both English and Indonesian. The findings confirmed that rosella flower petal extract inhibits the growth of various bacteria due to its high concentrations of flavonoids and anthocyanins. These results highlight its potential as a natural antibacterial agent. Rosella extract offers promising antibacterial benefits, supporting its use in health care and as a natural alternative in managing bacterial infections. Further research could expand its applications in medical and pharmaceutical fields.